Fractal Substructure of a nanopowder generated by repeated fragmentation and sedimentation: The role of the dust - Topic, Nikola; Wolf, Dietrich E.; Pöschel, Thorsten (Granular Matter, 2016)
Packings of cohesive nanoparticles, that is nano powders, may be obtained as the result of repeated fragmentation–reagglomeration cycles (Schwager et al. in Phys Rev Lett 100:218002, 2008) such that the resulting sediment reveals a fractal structure. The size distribution of the fragments after a fragmentation step is a superposition of a narrow distribution of large particles (chunks) whose size is determined by the cutting length and a power-law distribution for small particles, representing scale invariant dust. It was shown that the exponent of the power-law, τ , is in non-trivial relation to the fractal dimension, d f , via d f (2 − τ ) = 1. This poses the question for the structure of the sediment created by repeated fragmentation–reagglomeration cycles when the dust particles are excluded from the reagglomeration step. We found that even in this case, repeated fragmentation-reagglomeration cycles yield a sediment of fractal structure with slightly reduced fractal dimension while the dust exponent, τ , remains unchanged.